Modeling and simulation of switched reluctance motor (Balkan Journal of Applied Mathematics and Informatics, 2022)
This paper sets out the basics of Switched Reluctance Motor (SRM), its principle of operation and basic model. A simulation of SMR model in Simulink is presented and its operation is explained. This basic model od SRM operates with turn-on and turn-off angles of 45°C and 75°.  Next, on the basic model of SRM in Simulink, changes were made in the converter turn-on and turn-off angles. The new characteristics of the motor were presented, and the conclusions were derived about the impact of variation of turn-on and turn-off angles on the motor’s characteristics. Also, a load of 50 Nm has been added to the unloaded basic model of SRM and the obtained operating characteristics of the motor are presented.
Keywords: Switched Reluctance Motor, turn-on and turn-off angles, Flux Characteristic, Current Characteristic, Torque Characteristic, Speed Characteristic